Student's readiness, compentencies and skills in using online learning in preserving student's critical thinking - Elnetthra Folly Eldy (2015)
Problem-Based Learning (PBL) is a learning approach, designed where students as a focus of learning. Normally, PBL conducted face-to-face, however with recent rapid development of technology enables PBL to be implemented through online (PBL online). This study is done based on two main objectives: (i) to seek whether the previous or prior PBL online strategy can preserve Physics students’ critical thinking, and (ii) to recommend what is the best PBL online practices in order to preserve physics students’ critical thinking. PBL online was implemented into twenty five (25) second year students of Physics with Electronics at University Malaysia Sabah for twenty eight (28) weeks, corresponding to two semester study in two different Physics courses (i.e., Thermodynamics Physics and Statistical Physics). Watson Glaser Critical Thinking Appraisal (WGCTA) (1980) test was used as a main instrument to study the level of students’ critical thinking skills, there are five criteria of WGCTA to evaluate critical thinking: (i) making an inference; (ii) making an assumption; (iii) deduction; (iv) making an interpretation; and (v) evaluation argument. Findings also supported by survey questionnaire to study on students’ background and their level of computer usage in learning and readiness on learning via online learning. This study design as a quantitative methodology and described as one-group pretest-posttest design employ in quasi-experimental which design without control group. Results of Mann-Whitney U test and Independent Sample t- Test showed no significance difference in overall for critical thinking but as results was further analysis, it is identified that statistically significant difference for making an inference and making an interpretation on first phase of implementation while only making an inference was statistically significant difference on second phase. This finding was believed result from the nature of the subjects of PBL being implemented. Moreover, results also show the students’ critical thinking being preserved nay there is a positive improvement. Students’ perceptions and readiness towards PBL and PBL online were positive but proper strategy is needed for better results. Recommendation on best PBL online practices implement in sciences courses also proposed.